Urgency Development of National Law That is Oriented in the Protection of Human Rights Learning from Cases of Human Rights Violations - Derita Prapti Rahayu, Achmad Irwan Hamzani, Mukhidin dan (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
The development of national law is still in process. The national law in the futuremust provide certainty of the protection of human rights. The flow of globalizationhas given every citizen broad access to understand the value and concept of humanrights protection. The problems in this research are: How is the concept of humanrights in Indonesia? 2) How are the human rights violations occurring in Indonesiaand the settlement efforts? 3) How is the urgency of the development of nationallaw that is oriented towards the protection of human rights in the future? Thisresearch uses normative approach. The research data used is secondary data in theform of library materials. The analysis used the induction-interpretationconceptualization.The results of this study show: human rights are a fundamentalright. Every human being has a degree, dignity and equal rights. Many grosshuman rights violations in Indonesia. Human Rights Court ever held in Indonesiayet, but considered to be blunt. Development of national laws on the protection ofhuman rights should be oriented in line with the global demands that each countrymust uphold human rights.Keywords : Development of national law, orientation, human rights.